Sediment Transport Modeling at the Bogowonto River Bend Using HEC RAS 6.6 - Purwantoro, Didik; Yekti, Mawiti Infantri; Ratnaningsih, Rossita Yuli; Rofi’ah, Nanda Nur; Mayra, Farah (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2025)
River bend erosion is a major concern for river engineers because it affects channel stability and navigation safety. Erosion along the outer bank and deposition along the inner bank are the primary processes responsible for the meandering pattern of rivers. This study investigates the effect of discharge variations on scour depth in a meandering reach of the Bogowonto River using numerical modeling with HEC-RAS 6.6. Simulations were carried out for six discharge scenarios corresponding to return periods of 2,5, 10, 20, 50, and 100 years (Q2, Q5, Q10, Q20, Q50, and Q100). The historical rainfall data collected from 2002 to 2021. Limantara Unit Hydrograph used for rainfall-runoff modelling. The HEC-RAS simulation results of the 2-year return period (Q2) reveal that sedimentation occurs at five points along the Bogowonto River bend in Purworejo District. In particular the greatest accumulation occurred at the apex of the bend (STA 17), where the bed sediment thickness reached 4.175 m at the Q100 discharge. The simulation results show a uniform sedimentation pattern across the entire bend cross-section, likely due to model limitations that prevent detailed representation of cross-flow patterns.